2018
DOI: 10.1111/jors.12386
|View full text |Cite
|
Sign up to set email alerts
|

Compensation modes of border effects in cross‐border regions

Abstract: Both international and regional economics discuss borders as barriers to economic growth. They hamper trade flows between areas sharing an international border (a demand effect), as well as causing firms’ inefficiency because of the increase in production costs (supply side). In the theoretical and empirical discussions, no question has been raised on whether regional economies are able to set up compensation mechanisms, by replacing low endowments with high efficiency in the use of existing assets, or by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Different levels of employment lead to a consolidation of complete specialization, but also to an increase in the convergence process between the regions. What is important in the study, however, is the fact that both regions have taken measures (Capello, Caragliu, & Fratesi, 2018;Fratesi & Rodr ıguez-Pose, 2016).…”
Section: Period Onementioning
confidence: 99%
“…Different levels of employment lead to a consolidation of complete specialization, but also to an increase in the convergence process between the regions. What is important in the study, however, is the fact that both regions have taken measures (Capello, Caragliu, & Fratesi, 2018;Fratesi & Rodr ıguez-Pose, 2016).…”
Section: Period Onementioning
confidence: 99%
“…Furthermore, while some authors found that border effects in North America (Brown & Anderson, ) as well as in Europe (Nitsch, ) were declining, other studies suggest that a total reduction of border effects might be illusory, as defunct historical borders have persistent effects on trade, even when formal political barriers are absent (Nitsch & Wolf, ). The most recent advances in this strand of literature were dedicated to the decomposition of border effects and the examination of how the different obstacles posed by political borders (e.g., physical, institutional, cultural) impede economic development in cross‐border regions (Capello, Caragliu, & Fratesi, ; Capello, Caragliu, & Fratesi, ; Capello et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The European Union (EU) has been supporting cross-border cooperation through programs such as Interreg for over 25 years (Capello et al, 2018) or the creation of the Shengen area. Tourism is one of the main areas of this cooperation.…”
Section: Introductionmentioning
confidence: 99%